1983
DOI: 10.1111/j.1365-2842.1983.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of composites of selected shades in white light

Abstract: Light reflectivity, scattering coefficient, absorption coefficient, infinite optical thickness, and contrast ratio were determined in white light, for seven shades of a conventional composite and five shades of a microfilled composite, from reflection spectrophotometric data using Kubelka's equations. Significant differences among shades were observed for each property. Values of infinite optical thickness ranged from 2.97 to 5.90 mm among the shades studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…The thickness of the specimens was 2 mm, which was lower than infinite optical thickness 17 ; however, since the standard white background (CIE L* ϭ 96.7, a* ϭ Ϫ0.1, and b* ϭ Ϫ0.2, average reflectance from 400 to 700 nm ϭ 91.6%) was used, and the clinical thickness of anterior dental restorations is generally less than 2 mm, color measured in the present study has clinical relevance. There were significant correlations between ⌬E* ab values and ⌬E 99 values after polymerization and thermocycling (r ϭ 0.77 and 0.68, respectively, P Ͻ 0.01).…”
Section: Discussionmentioning
confidence: 98%
“…The thickness of the specimens was 2 mm, which was lower than infinite optical thickness 17 ; however, since the standard white background (CIE L* ϭ 96.7, a* ϭ Ϫ0.1, and b* ϭ Ϫ0.2, average reflectance from 400 to 700 nm ϭ 91.6%) was used, and the clinical thickness of anterior dental restorations is generally less than 2 mm, color measured in the present study has clinical relevance. There were significant correlations between ⌬E* ab values and ⌬E 99 values after polymerization and thermocycling (r ϭ 0.77 and 0.68, respectively, P Ͻ 0.01).…”
Section: Discussionmentioning
confidence: 98%
“…In such situations, opaque-shade resin composites have been utilized. 12,[14][15] Charisma was selected in this study because, in a previous study, this product showed a relatively small change in TP and color during light curing, 10 while the remainder of the products are newer resin composites. In this study, the A2 and opaque A2 shades of Charisma showed a statistically significant increase in TP.…”
Section: Discussionmentioning
confidence: 99%
“…20 Color measurement over the background of the corresponding material itself (cured, 2 mm thick) was performed to determine the inherent color of a material, 21 although the infinite optical thickness of these materials might be thicker or thinner than 4 mm because those of resin composites were in the range of 2.97-5.90 mm reported in a previous study. 22 The measurement was made after overlaying a specimen on another specimen of the cured same material. For example, to measure the color of ESF, the corresponding background was the cured ESF itself.…”
Section: Measurement Of Colormentioning
confidence: 99%